2014
DOI: 10.1111/obr.12221
|View full text |Cite
|
Sign up to set email alerts
|

Reward processing in obesity, substance addiction and non‐substance addiction

Abstract: Similarities and differences between obesity and addiction are a prominent topic of ongoing research. We conducted an activation likelihood estimation meta-analysis on 87 studies in order to map the functional magnetic resonance imaging (fMRI) response to reward in participants with obesity, substance addiction and non-substance (or behavioural) addiction, and to identify commonalities and differences between them. Our study confirms the existence of alterations during reward processing in obesity, non-substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
111
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 132 publications
12
111
2
Order By: Relevance
“…Since overeating, particularly of highly palatable foods, can affect the dopaminergic and opioidergic brain systems, the development of addiction-like behavior has to be considered (Daws et al, 2011). The issue is critical in urban youngsters because the behavioral and neurochemical overlap between overeating highly palatable foods, alcohol and cocaine drug addiction, insulin signaling and regulation of dopamine neurotransmission (Daws et al, 2011;Murray et al, 2014;Engel and Jerlhag, 2014;Blum et al, 2014;García-García et al, 2014;Burghardt et al, 2012). The Reward Deficiency Syndrome (RDS) results from an impairment of the brain reward circuitry with a hypo-dopaminergic function (Blum et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Since overeating, particularly of highly palatable foods, can affect the dopaminergic and opioidergic brain systems, the development of addiction-like behavior has to be considered (Daws et al, 2011). The issue is critical in urban youngsters because the behavioral and neurochemical overlap between overeating highly palatable foods, alcohol and cocaine drug addiction, insulin signaling and regulation of dopamine neurotransmission (Daws et al, 2011;Murray et al, 2014;Engel and Jerlhag, 2014;Blum et al, 2014;García-García et al, 2014;Burghardt et al, 2012). The Reward Deficiency Syndrome (RDS) results from an impairment of the brain reward circuitry with a hypo-dopaminergic function (Blum et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…In rodent studies, it has been demonstrated that drug-naïve high impulsive individuals are more likely to engage in drug self-administration than their low impulsive littermates (Dalley et al, 2007). Interestingly, drug dependency shares several similarities with obesity (García-García et al, 2014;see Volkow et al, 2013, for a review). Thus, a tendency to unpremeditated behaviour might also be a precursor of the transition from goal-directed (reward-driven) to habit-like (stimulus-driven) food consumption.…”
Section: From Habits To Compulsivitymentioning
confidence: 96%
“…Additionally, functional neuroimaging studies have observed differences between participants with obesity and normal-weight controls during reward processing. In response to food stimuli, participants with obesity exhibited higher activation of the parahippocampal gyrus/amygdala, putamen and superior frontal gyrus, along with lower activation of the insula and occipital areas (Nummenmaa et al, 2012;Brooks Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/psychresns García-García et al, 2014). To summarize, relative to normal-weight controls, participants with obesity seem to present a widely distributed pattern of structural and functional brain differences.…”
Section: Introductionmentioning
confidence: 95%